2022
DOI: 10.20473/ovz.v11i3.2022.103-108
|View full text |Cite
|
Sign up to set email alerts
|

Determination of estrus in Aceh cows based on the van Eerdenburg method

Abstract: Accurate determination of estrus status in an animal based on an appropriate estrus detection method can guarantee the cows' pregnancy after mating. This study aims to determine the estrus status of Aceh cows using the van Eerdenburg estrus behavior scoring method. This study was conducted from 22 January to 12 February 2021, at the Technical Implementation Unit for Animals of the Faculty of Veterinary Medicine, Universitas Syiah Kuala, Banda Aceh, Indonesia. The sample used was eleven Aceh cows aged 4-6 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In intensive rearing, the farmer's interaction with the cows was more frequent, so the observation of estrus should be better than in semi-intensive rearing (Sulfiar et al, 2022). The best signs of estrus that resulted in pregnancy after insemination must be comprehensive, including redness, visible swelling and warmth on the vulva, mucus discharge, bellowing, mounting, and standing to be ridden by another cow (Ramadhana et al, 2022). In this study, complete signs of estrus were observed in 60% of Limpo F1 cows and 63% of Limpo F2 cows, whereas in PO cows only 37%.…”
Section: Services Per Conceptionmentioning
confidence: 99%
“…In intensive rearing, the farmer's interaction with the cows was more frequent, so the observation of estrus should be better than in semi-intensive rearing (Sulfiar et al, 2022). The best signs of estrus that resulted in pregnancy after insemination must be comprehensive, including redness, visible swelling and warmth on the vulva, mucus discharge, bellowing, mounting, and standing to be ridden by another cow (Ramadhana et al, 2022). In this study, complete signs of estrus were observed in 60% of Limpo F1 cows and 63% of Limpo F2 cows, whereas in PO cows only 37%.…”
Section: Services Per Conceptionmentioning
confidence: 99%